Efficacy of Pharmacist Based Diabetes Educational Interventions on Clinical Outcomes of Adults With Type 2 Diabetes Mellitus: A Network Meta-Analysis - Bukhsh, Allah; Khan, Tahir M.; Lee, Shaun W. H.; Lee, Learn-Han; Chan, Kok-Gan; Goh, Bey-Hing (Frontiers in Pharmacology, 2018)
Background Comparative efficacy of different pharmacist based interventions on glycemic control of type 2 diabetes patients is unclear. This review aimed to evaluate and compare the efficacy of different pharmacist based interventions on clinical outcomes of type 2 diabetes patients. Methods A systematic search was conducted across five databases from date of database inception to September 2017. All randomized clinical trials evaluating the efficacy of pharmacist based interventions on type 2 diabetes patients were included for network meta-analysis. The protocol is available with PROSPERO (CRD42017078854). Results A total of 43 studies, involving 6259 type 2 diabetes patients, were included. Network meta-analysis demonstrated that all interventions significantly lowered glycosylated hemoglobin (HbA1c) levels compared to usual care, but there was no statistical evidence from this study that one intervention was significantly better than the other for reducing HbA1c levels. Pharmacist based diabetes education plus pharmaceutical care showed maximum efficacy for reducing HbA1c levels [-0·86, 95% CI -0·983, -0·727; p<0·001]. Pharmacist based diabetes education plus pharmaceutical care was observed to be statistically significant in lowering levels of systolic blood pressure [-4·94; 95%CI -8·65, -1·23] and triglycerides levels [-0·26, 95%CI -0·51, -0·01], as compared to the interventions which involved diabetes education by pharmacist, and for body mass index [-0·57; 95%CI -1·25, -0·12] in comparison to diabetes education by health care team involving pharmacist as member. Conclusion The findings of this review demonstrate that all interventions had a significantly positive effect on HbA1c, but there was no statistical evidence from this study that one intervention was significantly better than the other for achieving glycemic control. Pharmacist based diabetes education plus pharmaceutical care showed maximum efficacy on HbA1c and rest of the clinical outcomes.